(untitled) (SCIENCE TIME JOURNAL, 2024)
The article examines the history of the emergence and development of the concept of human and civil rights, how this concept has become an integral part of legal relations in society. The author also analyzes the current problems in the field of human and civil rights in the Republic of Uzbekistan, as well as existing problems, and puts forward a number of ideas as a solution to the problem.